Apocalyptic Eschatology: Lutheran‐Pentecostal Reflections on the End. Issue 4 (December 2016) - Chan, Michael J.; Miller, Joshua C.
Abstract: This paper initiates a Lutheran‐Pentecostal conversation around the topic of apocalyptic eschatology. Both groups have deep historical commitments to the apocalyptic theology of the Bible, even though they often have expressed these commitments in vastly different ways. We offer a historical and constructive outline of Lutheran apocalyptic eschatology, drawing attention to points of consonance and dissonance vis‐à‐vis Pentecostal forms of eschatology. We conclude with a series of generative questions that are meant to shape future Lutheran‐Pentecostal exchanges.